2019
DOI: 10.1101/719807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mining the human tonsillar microbiota as autoimmune modulator

Abstract: Palatine tonsils are important lymphoid organs featuring constant cross-talks between the commensal microorganisms and immune system, and have been implicated as critical autoimmunity origins for immune-related diseases, including rheumatoid arthritis (RA), a common autoimmune disorder. However, there was no evidence to show link between tonsillar microbiota and RA. Here, we identified a significant dysbiosis of RA tonsillar microbiota, with loss of Streptococcus salivarius and its functional molecules salivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Oral virome was more sensitive than other body sites to the environmental changes such as antibiotics taking [39]. In both untreated and treated RA patients, we found that the RA-associated changes of oral virome were remark ably greater than that of gut virome, so as in the bacterial metagenomic studies, suggesting that the oral microbiota could be the autoimmune regulator for its high correlation with host systemic autoimmune features[6, 40, 41]. Notably, in the oral virome, 57dental plaque and 463 saliva vOTUs had significantly differed in abundance among untreated/treated RA patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Oral virome was more sensitive than other body sites to the environmental changes such as antibiotics taking [39]. In both untreated and treated RA patients, we found that the RA-associated changes of oral virome were remark ably greater than that of gut virome, so as in the bacterial metagenomic studies, suggesting that the oral microbiota could be the autoimmune regulator for its high correlation with host systemic autoimmune features[6, 40, 41]. Notably, in the oral virome, 57dental plaque and 463 saliva vOTUs had significantly differed in abundance among untreated/treated RA patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%